Pengaruh Current Ratio Dan Return On Asset Terhadap Harga Saham Perusahaan Manufaktur - Sari, Laynita; Rahmadani, Aprila; Septiano, Renil (Fakultas Ekonomi Universitas Gresik, 2023)
The Covid-2019 pandemic is said to have suppressed people's purchasing power. The phenomenon that occurred in the Share Price of Indofood Sukses Makmur Tbk Manufacturing Company listed on the Indonesia Stock Exchange showed that from 2019-2020 it experienced a decline that was not in accordance with its target, where the Share Price in 2019 had a share price of Rp.7,925 per share, in 2020 it had a share price of Rp.6,825 per share. This shows that the Share Price of Indofood Sukses Makmur Tbk Manufacturing Company has experienced a considerable decline where the stock price's ability to make a profit is now being disrupted and is the cause of the economic situation that is still unstable due to the Covid-19 pandemic. But Indofood Sukses Makmur Tbk Manufacturing company has risen and returned because society has begun to adapt as before. This study aims to determine the effect of current ratio and return on assets on stock prices. With purposive sampling techniques, the population was sampled with a total sample of 11 manufacturing companies in the food and beverage subsector in 2016-2020. The analysis method used is a panel regression model. The results showed that the current ratio did not affect the share price of food and beverage companies listed on the Indonesia Stock Exchange in 2016-2020, while the return on assets had a positive and significant effect on the share prices of food and beverage companies. listed on the Indonesia Stock Exchange in 2016-2020.